2014
DOI: 10.1088/0067-0049/210/2/21
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarian Opacity Model for Aggregate Particles in Protoplanetary Nebulae and Exoplanet Atmospheres

Abstract: As small solid grains grow into larger ones in protoplanetary nebulae, or in the cloudy atmospheres of exoplanets, they generally form porous aggregates rather than solid spheres. A number of previous studies have used highly sophisticated schemes to calculate opacity models for irregular, porous particles with size much smaller than a wavelength. However, mere growth itself can affect the opacity of the medium in far more significant ways than the detailed compositional and/or structural differences between g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 84 publications
4
49
0
Order By: Relevance
“…This is confirmed by Fig. 10 in Cuzzi et al (2014): from the figure it becomes clear that the wavelength-independent geometrical limit for Q (and therefore our approximation) is applicable for grains of 10 µm if the temperature is larger than 300 K, and for grains of 100 µm (or larger) if T > ∼ 50 K. These conditions are usually met in protoplanetary atmospheres except for the advection regime where the grains remain small in the outer layers of the atmosphere. Fortunately, this regime occurs only when the planet is already at or close to the critical core mass, so that the impact on the total formation history of a planet remains small (Sect.…”
Section: Extinction Coefficient Qsupporting
confidence: 76%
See 3 more Smart Citations
“…This is confirmed by Fig. 10 in Cuzzi et al (2014): from the figure it becomes clear that the wavelength-independent geometrical limit for Q (and therefore our approximation) is applicable for grains of 10 µm if the temperature is larger than 300 K, and for grains of 100 µm (or larger) if T > ∼ 50 K. These conditions are usually met in protoplanetary atmospheres except for the advection regime where the grains remain small in the outer layers of the atmosphere. Fortunately, this regime occurs only when the planet is already at or close to the critical core mass, so that the impact on the total formation history of a planet remains small (Sect.…”
Section: Extinction Coefficient Qsupporting
confidence: 76%
“…2.7. We found that the results are again very similar because the grains are so large and the temperature sufficiently high that we are in the wavelength-independent regime (Cuzzi et al 2014). …”
Section: Settling Velocity Dust Density and Extinction Efficiencysupporting
confidence: 57%
See 2 more Smart Citations
“…We have also derived a semianalytical formula and confirm the fact that the absorption opacity is characterized by af except for the compact grains at the wavelengths of D 2 a (see Kataoka et al 2014). We also note that Cuzzi et al (2014) obtained similar conclusions on the opacity of porous dust aggregates.…”
Section: Opacity Evolutionsupporting
confidence: 76%